The Effect Of Think Talk Write (TTW) Towards On Ability To Solve Math Story Questions In SD Negeri Tidung Rappocini District Makassar City - Erita Novianti; Nurhaedah Nurhaedah; Suarlin Suarlin (International Journal of Elementary School Teacher, 2021)
This research aim to find out the effect of Think,Talk,Write (TTW) Learning Model Toward On Ability to Solve Math Story Questions in IV grade at SD Negeri Tidung Kecamatan Rappocini Kota Makassar. The Problem of this research were (1) How was the description of implementation Think,Talk,Write (TTW) Learning Model ? (2) What was the extend of the effect of Think,Talk,Write (TTW) Learning Model Toward On Ability to Solve Math Story Questions?. The purpose of this research were (1) to know the description of implementation Think,Talk,Write (TTW) Learning Model (2) to know the extend of the effect of Think,Talk,Write (TTW) Learning Model Toward On Ability to Solve Math Story Questions. The approach used in this research was quantitative  with the type of experimental  research. The research design used quasi experiment. The research variables consist of independent variables were Think, Talk, Write (TTW) learning models and the dependent variable was the ability to solve Math Story Questions. Data collection techniques using tests, observations and documentation. Data analysis techniques used descriptive statistical analysis and inferential statistical analysis. The results showed that: (1) The implementation of Think, Talk, Write (TTW) models on teacher observation activities took place very effectively and observations of student activities took place effectively. (2) Think, Talk, Write (TTW) learning model significantly influences the ability to solve Math Story Questions for IV grade students of SD Negeri Tidung Rappocini District, Makassar City. The effect can be seen from the differences in posttest results between the control group and the experimental group. The conclusion in this research was the use of Think, Talk, Write (TTW) learning model there is significant influence Toward On Ability to Solve Math Story Questions in Fourth Grade in SD Negeri Tidung Rappocini District, Makassar City